Simulation Study of the Damage Mechanisms Appearing in a Cross Ply Composite Material Loaded in Uniaxial Tension - Tsivolas Eleftherios (EDP Sciences, 2021)
The objective of this paper is to predict the different damage mechanisms in multiple scales that can occur in a cross ply composite material loaded in uniaxial tension. The simulated composite material consists of four epoxy-glass fibre layers [0/90]s and the material of each layer is transversely isotropic with viscous effects that occurred from micromechanical homogenization using Mori-Tanaka formulation, extended for visco-elastic materials. For the prediction of the cracking and interlaminar delamination, cohesive contacts were used and the final crack density results were compared with the corresponding experimental ones. Finally a microscale analysis was performed in a Representative Volume Element (RVE) to observe the matrix cracking behaviour in smaller scale.